New epoxy composite polymers as a potential anticorrosive coatings for carbon steel in 3.5% NaCl solution: Experimental and computational approaches - Hsissou, Rachid; Benhiba, Fouad; Echihi, Siham; Benkhaya, Said; Hilali, Miloudi; Berisha, Avni; Briche, Samir; Zarrouk, Abdelkader; Nouneh, Khalid; Elharfi, Ahmed (Chemical Data Collections, 2021)
•Two new epoxy composite polymers were investigated as potential anticorrosive coatings.•Epoxy composite polymer (SER/MDA) coating showed higher protective efficiencies for EIS (93.2%) and PDP (92.7%).•SEM analysis showed that the both epoxy composite polymers could effectively retard chloride ions attack owing to layer protective formed on CS area.•Computational approaches support experimental data and both composite polymers could be employed as potential anticorrosive coatings for CS in NaCl medium. Herein, diglycidyl bis disulfide carbon ether of bisphenol A sulfur epoxy resin (SER) crosslinked through hexamethylene diamine (HMDA) and methylene diamine (MDA) were investigated as a potential anticorrosive coatings for elevating carbon steel protection in sodium chloride (3.5% NaCl) solution using electrochemical and theoretical analysis. Potentiodynamic polarization data showed that the epoxy composite coatings investigated in 3.5% NaCl solution lateness the anticorrosive coatings and present the maximum protective efficiency obtained 97.9% in the presence of the sulfur epoxy resin crosslinked by MDA (SER/MDA) composite coating. Electrochemical impedance spectroscopy results indicate that the composite coatings employed retard the corrosion inhibition and have a higher protective efficiency compared with controlled (3.5% NaCl). Scanning electron microscope result displayed that the both SER/HMDA and SER/MDA composite polymers could be significantly retard chloride ions attack. Density functional theory calculations, Monte Carlo and molecular dynamics computational approaches support our experimental data. [Display omitted]